PENGALAMAN KELUARGA DALAM PENGAMBILAN KEPUTUSAN PADA PASIEN KRITIS DI RUANG INTENSIVE CARE UNIT (ICU) RSUD ULIN BANJARMASIN - Hafifah, Ifa; Fitrhriyah, Noor (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2018)
Family experience when making decisions in critical patients is not an easy thing. Foundmany problems experienced by the family when making decisions such as physiological,psychological, spiritual, social, and cultural issues. Those problems must be overcomeand the resulting decision is the best decision for the patient and the patient's family. Theaim of this research was to explore about family’s experiences in making decision incritical patients. The research design used qualitative research with descriptivephenomenology approach. This research have been done in ICU ofUlin Hospital on July20 to August 6, 2017. The number of informants had reached saturation that was 7informants family of critical patients in ICU. The techniques of data collection in thisstudy has been used in-depth interviews. Data analysis used thematic analysis of Braunand Clarke. The Result found that 6 themes are discussions with family-related to patientcare, information about the action to be taken, patient's cure a top priority, length ofpatient care, patient care funding, and family involvement in patient care. The Advice fornurses and health personnel are to provide all needs of services that must be given to thefamily before making decision.